Transformation of capitalism to enforce ecologically sustainable GDP growth: lessons from Keynes and Schumpeter - Hansjörg Herr (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
An economy with a low stable medium-term growth rate given by ecological needs is only possible after a radical reform of the type of capitalism we have today. In an ecologically sustainable economic system, aggregate demand has to be controlled on a macroeconomic level. Of focal importance is the steering of investment. Here a national credit plan that fixes the national credit volume and to a certain extent the allocation of credit is in the centre. For consumption demand in a low-growth economy it is important that saving is low or in a zero-growth economy even zero, whereas at the same time accumulation of deficits of economic sectors or sub-sectors such as poorer households are not sustainable. Here policies to achieve a more equal distribution of income and wealth are suitable. Although comprehensive government interventions and rules are needed in an ecologically low-growth economy, the recommended system is not comparable with a planned system of the former Soviet type. Whether such an alternative system is understood as a version of highly regulated capitalism or as a new system is a question of taste.
Keywords: 330; ecological transformation; low-growth economy; credit planB20; B52; P41